An integrated approach to distance learning with digital video in the French-speaking Virtual Medical University - Dufour, J.C.; Cuggia, M.; Soula, G.; Spector, M.; Kohler, F. (International journal of medical informatics (Shannon, Ireland), 2007)
The aim of the French-speaking Virtual Medical University project (UMVF) is to share common resources and specific tools in order to improve medical training. Digital video on IP is an attractive tool for higher education but there are a number of obstacles to widespread implementation. This paper describes the UMVF approach to integrating digital video technologies and services in educational projects.